2021
DOI: 10.1021/acs.jced.1c00653
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibrium of Methane Hydrate Encapsulated Isotopologue 13CH4 and Singly Deuterated Methane

Abstract: Hydrate equilibrium conditions for 13CH4 were measured for temperatures ranging from 270 to 278 K and for pressures ranging from 2.3 to 4.2 MPa. The equilibrium pressure values in a 13CH4–H2O system were nearly the same as those in a 12CH4–H2O system. The similarity between the equilibrium pressures for these two systems can be used to explain why an existing study found nearly no fractionation of CH4 carbon isotopes during the formation of synthetic CH4 hydrates. We also measured the hydrate equilibrium condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…The experimental results of the hydrogen stable isotope fractionation of methane during methane hydrate formation suggested that the equilibrium pressure of the CH 3 D hydrate is greater than that of the CH 4 hydrate, which was confirmed by measurements of their equilibrium pressures . In contrast, the stable isotope fractionation of carbon in methane during methane hydrate formation was negligible and below the detection limits, ,, which is consistent with the observation that the equilibrium pressures of the 13 CH 4 and 12 CH 4 hydrates are similar . This type of stable isotope fractionation of guest gases has been reported for ethane, carbon dioxide, , and hydrogen sulfide, as well as methane …”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…The experimental results of the hydrogen stable isotope fractionation of methane during methane hydrate formation suggested that the equilibrium pressure of the CH 3 D hydrate is greater than that of the CH 4 hydrate, which was confirmed by measurements of their equilibrium pressures . In contrast, the stable isotope fractionation of carbon in methane during methane hydrate formation was negligible and below the detection limits, ,, which is consistent with the observation that the equilibrium pressures of the 13 CH 4 and 12 CH 4 hydrates are similar . This type of stable isotope fractionation of guest gases has been reported for ethane, carbon dioxide, , and hydrogen sulfide, as well as methane …”
Section: Introductionsupporting
confidence: 86%
“…14 In contrast, the stable isotope fractionation of carbon in methane during methane hydrate formation was negligible and below the detection limits, 12,15,16 which is consistent with the observation that the equilibrium pressures of the 13 CH 4 and 12 CH 4 hydrates are similar. 17 This type of stable isotope fractionation of guest gases has been reported for ethane, 12 carbon dioxide, 15,18 and hydrogen sulfide, 19 as well as methane. 12 The objective of this study is to determine the stable isotope fractionation factor of nitrogen during the formation of gas hydrate-encapsulated nitrogen.…”
Section: Introductionsupporting
confidence: 78%
“…Similarly, the stable isotope fractionation of guest molecules during the formation of gas hydrates may be explained by the differences in the inclusion properties of isotopologues: CH 3 2 H is less included than CH 4 , with a difference of 4.8 ± 0.4‰ in their δ 2 H values at 274.2 K [9] (δ values are defined in the Section 3), which is consistent with the slightly higher equilibrium pressures of CH 3 2 H hydrates than those of CH 4 hydrates [17]. Additionally, the negligible carbon isotope fractionation of methane during the formation of methane hydrates is consistent with the almost equal equilibrium pressures of the 13 CH 4 and 12 CH 4 hydrates [18].…”
Section: Introductionsupporting
confidence: 80%
“…In the phase equilibrium measurement, a porous sample of argon hydrate was formed in the pressure cell and an equilibrium condition was achieved without agitating the device. The method is the same as the previous work. , Approximately 10 g of fine ice powder was placed in the pressure cell and vacuumed at a temperature of 77 K. Argon gas prepared with the amount needed to achieve equilibrium conditions of the liquid water, hydrate, and vapor at 273.2 K was trapped in the cell at 77 K. Argon hydrate was formed by melting the ice powder at 273.2 K under high pressure of argon. The equilibrium pressure at each temperature was determined using a step-by-step isochoric method of heating and cooling.…”
Section: Methodsmentioning
confidence: 99%
“…The quadruple point is the four-phase (vapor + hydrate + ice + water) equilibrium condition of the argon–H 2 O system. The quadruple point of the argon–H 2 O system was determined via the same method as in previous studies. , To estimate the hydration number, the difference in dissociation enthalpy between phases of vapor + hydrate + ice and vapor + hydrate + water at the quadruple point of the argon–H 2 O system was used. This method of estimating the hydration number has been used in earlier studies. …”
Section: Methodsmentioning
confidence: 99%